Isotopic characteristics of carbon and oxygen within ordovician carbonate paleokarst in the tazhong region and their paleoenvironmental significance - Zhang, Qingyu; Liang, Bin; Ji, Shaocong; Li, Jingrui (Frontiers in Earth Science, 2023)
The Tazhong region is a key area for oil and gas exploration and development within the Tarim basin. In this region, development of Ordovician carbonate paleokarsts has been found to be extremely heterogeneous. To investigate the developmental stages of these Ordovician carbonate karsts and their corresponding paleoenvironmental conditions, oxygen and carbon isotopic characteristics of calcite paleokarst fissure fillings were examined in conjunction with rock-structure analyses. Results show that δ18O (PDB) values tend towards negative values in general, ranging from -3.97% to -12.7% (average value -7.64%), which is indicative of the presence of paleokarstification via dissolution by atmospheric freshwater. Values of δ13C (PDB) span a relatively large range, from 2.48% to -2.13% (average value of 0.23%). This shows that the paleokarst in this area has gone through two stages of supergene and burial diagenesis, and the process of paleokarst is complex. The paleotemperature at which the karst fissure-filling deposits were formed ranged from 6.5 to 47.1°C (average value of 21.8°C), and the salinity of the medium has Z values from 117.48 to 130.24 (average value of 123.94). Four different paleokarsification settings were thus revealed: a marine depositional environment, an atmospheric freshwater karst-filling environment, a shallow-burial paleokarsification environment and a deep-burial high-temperature environment. It has thus been shown that the karst pores, fissures and caves formed by paleokarstification over multiple stages are the main reservoir spaces in this region. This study will serves as a basis for karst reservoir predictions, and exploration and development in this region.